Síntese de ácidos 3-alcóxi-3-cianopropanóicos, ácidos 2-ciano tetraidrofuran(2h-piran)-3-óicos e sua aplicação na obtenção dos respectivos ácidos succinâmicos e succínicos - Silva, Fabio Machado da (2007)
This work presents the synthesis of a series of 3-alkoxy-3-cyanopropanoic acids and 2-cyanotetrahydrofuran(2H-pyran)-3-carboxylic acids of general formula HO2CCH(R2)CR1(OR)CN, where R/R2= Et/H, Et/Me, -(CH2)2-, -(CH2)3-, iso-Pr/H, sec- Bu/H, iso-Pr/Me, sec-Bu/Me and R1= H, obtained through the reaction of β-alkoxyvinyl trichloromethyl ketones [Cl3CCOC(R2)=CR1(OR)] with sodium cyanide. The methodology used in the synthesis provided high selectivity to the reaction, being observed only the formation of the expected products, through a conjugated addition the cyanide to the β-carbon of the enones and substitution of the CCl3 group by the hydroxyl ion originated from the basic medium used in the reaction. The β-alkoxyvinyl trichloromethyl ketones where R/R2= Et/H, R1= OEt and R/R2= Et/Br, R1=H, when submitted the same reaction conditions, furnished the succinimide 3,3-diethoxypyrrolidine-2,5-dione and the maleimide 3-ethoxy-1H-pyrrole-2,5-dione, respectively. In a second reaction, the synthesized 3-alkoxy-3-cyanopropanoic acids and 2- cyanotetrahydrofuran(2H-pyran)-3-carboxylic acids were used to obtain succinamic acids and succinic acids of general formula HO2CCH(R2)CR1(OR)CONH2 and HO2CCH(R2)CR1(OR)CO2H, respectively. The succinamic acids were formed by the spontaneous conversion of the cyano group to amide (partial hydrolysis) and the succinic acids were obtained by the total hydrolysis of the cyano group to carboxylic acid, under reflux and acid medium.